Cultural feminism versus post-structuralism: The identity crisis in feminist theory - Alcoff, Linda (Signs, 1988)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem9000; femmes*; identité sexuelle; philosophie; post-structuralisme; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; états-unis; études culturelles

chapitre 3, « Les couvents comme expression organisée des aspirations des femmes » dans Profession: religieuse : un choix pour les Québécoises, 1840-1920 - Danylewycz, Marta; Linteau, Paul-André; Prentice, Alison; Westfall, William (Profession: religieuse : un choix pour les Québécoises, 1840-1920, 1988)
Marta Danylewycz s'intéresse à 2 communautés: les soeurs de Notre-Dame et de la Miséricorde, qui rassemblent près du cinquième de la population religieuse féminine au tournant du siècle.
Section: 246 pages : illustrations ; 22 cm
Keywords: 1800-1899; 1840-1849; 1850-1859; 1860-1869; 1870-1879; 1880-1889; 1890-1899; 1900-1909; 1900-1999; 1910-1919; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; discours dominant; his4550; histoire; histoire et politique; patriarcat; premier cycle; périodes historiques; québec; religion; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques

Homeward bound: American families in the Cold War era - May, Elaine Tyler (Basic Books, 1988)
In the 1950s, the term "containment" referred to the foreign policy-driven containment of Communism and atomic proliferation. Yet in Homeward Bound May demonstrates that there was also a domestic version of containment where the "sphere of influence" was the home. Within its walls, potentially dangerous social forces might be tamed, securing the fulfilling life to which postwar women and men aspired. Homeward Bound tells the story of domestic containment - how it emerged, how it affected the lives of those who tried to conform to it, and how it unraveled in the wake of the Vietnam era's assault on Cold War culture, when unwed mothers, feminists, and "secular humanists" became the new "enemy." This revised and updated edition includes the latest information on race, the culture wars, and current cultural and political controversies of the post-Cold War era.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; amériques; approches et analyses; cold war; cours; discipline; division of household labor; division sexuelle du travail; famille; guerre froide; his4443; histoire; histoire des femmes*; histoire du féminisme; histoire et politique; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; thématiques; travail; travail domestique; états-unis

The sexual contract - Pateman, Carole (Standford University Press, 1988)
In this remarkably original work of political philosophy, one of today's foremost feminist theorist challenges the way contemporary society functions by questioning the standard interpretation of an idea that is deeply embedded in American and British political thought: that our rights and freedoms derive from the social contract explicated by Locke, Hobbes, and Rousseau and interpreted in the United States by the Founding Fathers.
Keywords: 1900-1999; 1980-1989; amériques; citoyenneté; contrat social; cours; discipline; droits des femmes*; fem1000; incontournable; philosophie politique; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques; théories féministes; états-unis